A3_11 “Take the Next Left …” at Olympus Mons - Booth, Tim; Ryan, Liam; Karazhov, Dennis (Physics Special Topics, 2011)
<!–[if gte mso 9]> 800x600 <![endif]–><!–[if gte mso 9]> Normal 0 false false false EN-GB X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> This paper analyses the effects due to special and general relativity on a GPS satellite orbiting at an altitude of 3 Mars radii. It was found that in order to keep both the ground station and the satellite in synchronisation the clock on the satellite would have to be 1.56 Î¼s per Martian day faster than the one on the ground.